Peran Penting Pendidikan Islam di Era Modern - Marsha Nur Amalia; Annisa Putri Ramadhani; Fitria Ika Farizha (CV. ITTC INDONESIA, 2024)
The research is based on awareness of the important role of Islamic education in the modern era. Islamic religious education is education based on Islam or an Islamic education system, namely education that is understood and developed and compiled from fundamental teachings and values ​​contained in its sources, namely the Al-Qur'an and hadith. The aim of this research is to explain the importance of the existence of Islamic education in the current modern era. Meanwhile, the research method adopts the literature review method, namely activities that consist of collecting library data, reading, recording and managing research materials. The results of this research are intended to support potential developments in the world of further education, especially in Islamic education..